"The Advent of Civilization Amongst Them Will Not Tend to Their Betterment": Understanding Representations of Colonial Contact in the Kitikmeot. - McLean, Scott (Journal of Canadian Studies)
Between 1915 and 1920, members of the Royal Northwest Mounted Police (RNWMP) wrote four major narratives of making contact with Inuit living in territory now known as the Kitikmeot region of Nunavut. The authors were the first representatives of the Canadian state to enter the region, and their narratives positioned Inuit as "better off without civilization." Various members of the Royal Canadian Mounted Police (RCMP) stationed in the region over the subsequent three decades reproduced such discourse. While, at first glance, this discourse seems to attribute a nobility to traditional ways of life, upon closer inspection it actually positions Inuit as incapable of adapting successfully to changing socio-economic circumstances. Methodologically, this article critically reinterprets archival documents from the early agents of colonization in the Kitikmeot. While advancing historical scholarship concerning relations between Inuit and the Canadian state, the article contributes to contemporary agendas of decolonization and reconciliation by enabling a more complete understanding of the origins and nature of colonial rule in the Arctic. By arguing that colonial discourses have roots in local and specific relations of production, the article also contributes to postcolonial theories of efforts to legitimize colonization and represent colonized Others in essentialist and paternalistic terms.